Effectiveness of Virtual Reality-Based Guided Imagery Intervention on Intradialysis Blood Pressure in Patients Undergoing Hemodialysis - Desnita, Ria; Sapardi, Vivi Syofia; Surya, Defrima Oka (Indonesian Journal of Global Health Research, 2024)
An increase in blood pressure during hemodialysis, known as intradialysis hypertension, if left untreated can lead to death in patients. Guided imagery therapy can provide a relaxing effect on patients to reduce sympathetic nerve overwork. The development of guided imagery therapy with virtual reality technology can project the visualization of objects more real to the patient so that it is expected to further relax the patient during hemodialysis so that blood pressure is stable. The purpose of this study was to determine the effectiveness of virtual reality-based guided imagery intervention on intradialytic blood pressure in hemodialysis patients. The research design was a quasi-experiment using a one-group pre and post-test with a control group approach. The research was conducted in the Hemodialysis Room of dr. Reksodiwiryo Padang hospital. Sampling using purposive sampling technique with a sample size of 13 people in each group. The mean difference in Mean Arterial Pressure in the intervention group before and after the intervention was 5.56, while in the control group, it was 0.51. The study was conducted from July – November 2023, blood pressure data is obtained by direct measurement and than mean arterial ressure was calculated. Data analysis using paired t test. The results of further analysis showed that there was a significant difference in the difference in pre-posttest MAP in the intervention group and control group (p = 0.001, α = 0.05) so it was concluded that Guided Imagery therapy based on Virtual Reality was effective in controlling intradialysis blood pressure. Guided Imagery therapy intervention based on Virtual Reality can be one of the therapies.